Effects of body weight vs. lean body mass on Wingate anaerobic test performance in endurance athletes - Galán-Rioja, M. A.; González-Mohino, F.; Sanders, D.; Mellado, J.; González-Ravé, J. M. (International Journal of Sports Medicine, 2020)
The aim of this study was to determine the influence of body weight or lean body mass-based load on Wingate Anaerobic Test performance in male and female endurance trained individuals. Thirty-one participants (22 male cyclists and triathletes and 9 female triathletes) completed two randomized Wingate Anaerobic Test (body weight and lean body mass loads) in stationary start. There were no significant differences in power outputs variables between loads in any group. However, when comparing specific groups within the sample (e. g. cyclists vs cyclists) medium to large effect sizes were observed for Relative Mean Power Output (ES=0.53), Relative Lowest Power (ES=0.99) and Relative Power Muscle Mass (ES=0.54). Regarding gender differences, male cyclists and triathletes displayed higher relative and absolute power outputs (p<0.001) compared to female triathletes regardless of the protocol used. FI was lower in female triathletes compared to male triathletes and cyclists in body weight (p<0.001) and lean body mass (p<0.01) protocols. Body composition and anthropometric characteristics were similar in male cyclists and triathletes, but there were differences between genders. These results suggest that using either body weight-based or lean body mass-based load can be used interchangeably. However, there may be some practically relevant differences when evaluating this on an individual level.